The Transformation of Acupuncture Practice Using Ultrasonography: Expert Opinions - Eunbyul Cho; Changsop Yang; Sungha Kim (Medical Association of Pharmacopuncture Institute, 2024)
Importance: The rapidly growing use of ultrasound in South Korea has revolutionized the real-world application of acupuncture, making it a safer, more accurate treatment. However, little is known about the challenges Korean medicine doctors (KMDs) encounter, as well as the procedures and resources necessary for hygienic, safe ultrasound-guided acupuncture. Objective: This study aimed to investigate the purpose, indications, and procedure for ultrasound-guided acupuncture in Korean medicine (KM) practice and the challenges KMDs encounter in using ultrasonography. Methods: Eleven KMDs with expertise in practicing or teaching ultrasonography were consulted in detail. The purpose of ultrasonography in real-world practice, the overall process, resources utilized in ultrasound-guided procedures, and the unaddressed needs of KMDs were investigated. Results: Ultrasound guidance, employed for various diseases in KM practice, is crucial for pharmacopuncture and acupotomy to increase accuracy and safety. Ultrasoundguided acupuncture involves covering the probe, putting on sterile gloves, and scanning with disinfectants, though the exact steps vary among experts. They also suggested that a lack of insurance coverage was a common obstacle for KMDs utilizing ultrasonography. Conclusions and Relevance: Acupuncture with ultrasound guidance has become a prevalent procedure in South Korea. Standard procedure guidelines and insurance coverage for ultrasonography used for acupuncture procedures are essential to ensure safe, accurate procedures.